(untitled) (Global Journal of Human-Social Science, 2021)
This paper discusses Francophone Pedigrees and Southern Cameroon Contagions in Bill Ndi s Peace Mongers at War by drawing on Mignolo s conception of the pluriverse Francophone Pedigrees refer to Francophone-imposed hegemonic benchmarks by which Anglophone Cameroon culture and politics are condescendingly assessed and self-assertingly dismissed Southern Cameroon Contagions designate readily convivial pluriversal and accommodating Anglophone cultures and politics downgraded by Francophones as pestilences or infestations The paper contends that Peace Mongers at War attests that in moments such as the ongoing Anglophone crisis dialogue cannot exist without humility and the naming of the Cameroonian polity cannot continue to be an act of Francophone Pedigrees arrogance The paper asserts that Francophones start from the premise that naming the Cameroonian world is the task of the Francophone elite and that the presence of Anglophones in history is a sign of deterioration that they are closed to and even offended by the contribution of Anglophones because they are afraid of being displaced